Eficácia do sururu (Mytella falcata) na recuperação de crianças desnutridas, moradoras de favelas – MACEIÓ-AL - Correia, Larissa Tenório Andrade (2012)
Childhood malnutrition, consisting of stunting is still a public health problem especially when associated with anemia together represent the most prevalent nutritional problems in many parts of the world. An alternative to recover these nutritional problems would be a balanced diet with food from regional low-cost and high nutritional density. In Alagoas, the mussels and coconut milk preparation are widely known and appreciated being linked to the culture of the state. Based on the above it is proposed to evaluate the effectiveness of mussels (Mytella falcata) and preparing mussels with coconut milk in the recovery of malnourished children living in slums - Maceió-AL. Thus, we evaluated 64 children chronically malnourished Z score <-2 for height for age index (A-I) aged between 12 and 71 months seen at the Recovery Center and Nutrition Education - CREN-AL. They were matched for age and degree of malnutrition forming three groups. All participants received a balanced diet for the nutritional differing only in protein supply. It was offered to group 1 (beef) meat preparation, group 2 (mussels - SS) preparation of mussels and group 3 (mussels with coconut milk - SCLC) is a preparation of mussels with coconut milk. The results indicated a decrease in the prevalence of malnutrition in all groups studied. The anthropometric evaluation at the end of the study revealed that children had an average increase in Z score of 0,72 for meat group, the group that received mussels 0,62 and 0,60 in the group treated of mussels with milk of coconut (p<0,05). Also, there was a reduction in the prevalence of anemia in all groups with percentage reduction of 22,8% (p=0,002), 27,8% (p=0,007) and 42,4% (p˂0,001) in groups of meat, SS and SCLC respectively. It follows therefore that the preparation mussels with and without coconut milk can be an effective substitute beef in combating child malnutrition and anemia, may be included on the menu and meals of children's institutions (kindergartens, schools) and programs aimed at recovering malnourished children.